21st Nationwide Common Entrance Examinations Mathematics And Quantitative Aptitude Tests - Ugo, Ugo C (Ugo C Ugo Publishing Company Limited, 2013)
This book helps pupils in Primary 5 and 6 in preparing for the National Common Entrance Examinations alone or with the assistance of their teachers.
Keywords: Common Entrance; Examination; Mathematics; Non Fiction